Creative thinking mathematical ability of students in Treffinger learning based on cognitive style - Nurzulifa, Siti; Dwijanto, Dwijanto (Department of Mathematics, Universitas Negeri Semarang, 2021)
This study aimed to test the thoroughness of learning Treffinger for mathematical creative thinking abilities of students, tes the mathematical creative thinking abilities of students in the learning Treffinger compared conventional, and analyze the mathematical creative thinking abilities of students in Treffinger based cognitive style. This study uses a mixed methods design sequential explanatory. The subjects of this study were six students of class VII J SMP Negeri 1 Godong in the even semester of the academic year 2018/2019. Data collection techniques used include: observation, documentation, test, and interviews. The result showed that (1) learning Treffinger due to the ability of creative thinking mathematically, (2) ability to think creatively mathematical students in learning Treffinger higher than the ability to think creatively mathematical students in learning conventional, (3) the ability to think creatively mathematically students on cognitive style is (a) field independent students less able to work on question smoothly and flexibly; can work on new problem correctly ; can write in detail and correctly what is known in the problem, can develop ideas that are owned by being able to draw geometric flat shapes well; (b) intermediet field students less able to work on question smoothly and flexibly; less able to work on new problem correctly; can develop ideas that are owned by being able draw geometry well; (c) field dependent student less able to work on question smoothly and flexibly; less able to work on new problems correctly; less able to develop ideas that have to work on a problem.